Analysis of Avalanche Phenomena in Developing Neuronal Circuits Cultured on Microelectrode Array. Issue 11 (November 2014) - Goto, Miho; Yoshida, Lui; Saito, Atsushi; Saito, Aki; Takayama, Yuzo; Moriguchi, Hiroyuki; Kotani, Kiyoshi; Jimbo, Yasuhiko
SUMMARY To analyze network dynamics, neuronal avalanche is a quite interesting phenomenon. Recently, it was reported that neuronal avalanches were power‐law distributed in a slice cortex of a rat, which attracted attention because power‐law behavior in neuronal avalanches is an important index representing network criticality and its efficiency of information transition. In this study, we focused on the early stage of network growth and observed avalanche phenomena during their development. Power‐law behavior in neuronal avalanches was observed at a matured stage, as reported in previous research. However, in the early stage, the size distribution of avalanches did not follow a power law, indicating that there was a transient period moving on to the critical point.